Pengembangan Produk Ecoprint Sebagai Inovasi Ramah Lingkungan Dalam Pemberdayaan UMKM Kreatif SD 040479 Desa Perteguhen - Ezika Aquilera Sitio; Rizky Amelia Siregar; Siska Kumala Sari; Fandi Ahmad Zain Dalimunthe; Silvia Tabah Hati (Sekolah Tinggi Ilmu Ekonomi Pariwisata Indonesia Semarang, 2026)
This community service activity was carried out by the Real Work Lecture (KKN) team of the State Islamic University of North Sumatra (UINSU) with the aim of developing ecoprint products as an environmentally friendly innovation as well as a means of empowering creative MSMEs in the environment of SD 040479 Perteguhen, Simpang Empat District, Karo Regency. This program was motivated by the low level of public awareness of the importance of sustainable natural resource management and the limited skills in utilizing the potential of the environment to create products with economic value. This activity is also expected to provide an educational experience for elementary school students in learning about environmentally friendly concepts and creative entrepreneurship from an early age. The activity was held on August 9, 2025, involving participants from among students, teachers, and the community around the school. The implementation method included four stages, namely (1) socialization and environmental education on the basic principles of ecoprint, (2) technical training in ecoprint making, (3) hands-on practice using natural materials, and (4) evaluation and reflection on the results of the work. The technique used was the method of soaking tote bags in hot water at a temperature of 80–90°C using natural materials such as teak leaves, guava leaves, cassava leaves, and hibiscus flowers available around the school. The results of the activity showed that the hot water soaking technique produced soft natural motifs, harmonious color gradations, and leaf patterns